Fever management in children and insights into fever of unknown origin: a survey among Italian pediatricians - Chiappini, Elena; Orlandi, Michela; Chiarugi, Alberto; Di Mauro, Antonio; Insalaco, Antonella; Milani, Gregorio Paolo; Vallini, Monica; Lo Vecchio, Andrea (Frontiers in Pediatrics, 2024)
Background. Fever is a common symptom in children, but despite existing guidelines, pediatricians may not fully apply recommendations. Fever of Unknown Origin (FUO) is generally referred to as an unexplained prolonged fever. However, a standardized FUO definition and management is missing. Objective. To collect updated data on the approach to fever and FUO among Italian pediatricians. Methods. A cross-sectional anonymous survey was conducted among a large sample of primary care and hospital pediatricians. The panel group formulated and proposed a practical FUO definition, using a modified Delphi approach. A 75% consensus was required to reach an agreement. Results. Among 620 respondents, paracetamol was the first-choice antipyretic for 97.7% of participants, followed by ibuprofen; 38.4% prescribed antipyretics based on a specific body temperature rather than on child’s discomfort, while physical methods were almost completely abandoned. Alternate treatment was recommended by 18.8% (123/620) of participants, 16.9% (105/620) would prescribe antipyretics to prevent adverse events following immunization. Regarding FUO diagnosis, 58.3% (362/620) considered as cut-off a body temperature above 38°C; the duration required was one week according to 36.45% (226/620) of participants, two weeks according to 35.32% (219/620). The FUO definition proposed by the expert panel reached 81% of consent. Large agreement was observed on first-level laboratory and instrumental investigations in the diagnostic evaluation of FUO, whereas more discrepancies arose on second and third-level investigations. Compared to what participants reported for the treatment of non-prolonged fever, a significant decrease in the prescription of paracetamol as first-choice drug in children with FUO was observed (80.5%; P < 0.0001). Interestingly, 39% of participants would empirically recommend antibiotics, 13.7% steroids, and 4.5% Nonsteroidal Anti-Inflammatory Drugs (NSAIDs) for persistent FUO. Conclusion: Non-recommended behaviors in fever management persist among pediatricians, including alternating use of paracetamol and ibuprofen, and their prophylactic use for vaccinations. Our data confirm the variability in the definition, work-up, and management of FUO. We observed that in children with FUO paracetamol was significantly less commonly preferred than in non-prolonged fever, which is not supported by evidence. Our findings combined with evidence from existing literature underlined the need for future consensus documents.